2022
DOI: 10.1101/2022.05.13.22275049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the humoral response to the homologous Gam-COVID-Vac (Sputnik V) or heterologous Sputnik V/mRNA-1273 (Moderna) vaccination against SARS-CoV-2 in dialysis patients

Abstract: Introduction: The humoral response to vaccines is the most used tool to evaluate the protection against SARS-CoV-2 infection. Dialysis patients are a high-risk population and have a reduced immune response to vaccination. Objective: To assess the humoral response to homologous Gam-COVID-Vac (Sputnik V) and heterologous Sputnik V/mRNA-1273 (Moderna) vaccination in dialysis patients. Methods: SARS-CoV-2 anti-spike IgG (RBD) concentration was estimated 3-16 weeks after complete vaccination. Reactogenicity was ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…Consequently, we feel that the analytical approach initially performed in our research is accurate. Finally, the immune response variations according to different boost vaccination schemes observed in our study were also registered in a subset of patients receiving dialysis 4 and confirmed by a recently published study that assessed the humoral response to several vaccination schemes, including the homologous prime-boost vaccination with Gam-COVID-Vac and the heterologous combination with mRNA-1273 (Moderna, Mod) vaccine 5 .…”
supporting
confidence: 86%
“…Consequently, we feel that the analytical approach initially performed in our research is accurate. Finally, the immune response variations according to different boost vaccination schemes observed in our study were also registered in a subset of patients receiving dialysis 4 and confirmed by a recently published study that assessed the humoral response to several vaccination schemes, including the homologous prime-boost vaccination with Gam-COVID-Vac and the heterologous combination with mRNA-1273 (Moderna, Mod) vaccine 5 .…”
supporting
confidence: 86%